2017
DOI: 10.1515/nleng-2016-0058
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer flow of dusty fluid over a radiating stretching surface embedded in a thermally stratified porous medium in the presence of uniform heat source

Abstract: Numerical investigation for the effect of thermal stratification on MHD flow and heat transfer of dusty fluid over a vertical stretching sheet embedded in a thermally stratified porous medium in the presence of uniform heat source and thermal radiation. The governing equations for the problem were reduced in to dimensionless ordinary differential equations using suitable similarity transformations. The transformed nonlinear ordinary differential equations are numerically solved by applying efficient RungeKutta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Numerical solution for steady boundary layer flow of dusty fluid over a radiating stretching surface embedded in a thermally stratified porous medium in the presence of uniform heat source was studied by Gireesha et.al. [20]. Recently, Ramzan et.al.…”
Section: Vidyanadha Babu and M Suryanarayana Reddymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical solution for steady boundary layer flow of dusty fluid over a radiating stretching surface embedded in a thermally stratified porous medium in the presence of uniform heat source was studied by Gireesha et.al. [20]. Recently, Ramzan et.al.…”
Section: Vidyanadha Babu and M Suryanarayana Reddymentioning
confidence: 99%
“…The equations (16) - (18) together with the boundary conditions (19) - (20) are integrated numerically by using Runge-Kutta-Gill method along with the shooting technique. This method is concisely outlined as below: (Ralston and Wilf [23]).…”
Section: Solution Of the Problemmentioning
confidence: 99%
“…Nandeppanavar et al [18] investigated heat transfer through a porous medium over a stretching sheet with effect of viscous dissipation. Gireesha et al [19], worked on boundary layer flow of dusty fluid over a radiating stretching surface embedded in a thermally stratified porous medium in the presence of uniform heat source. They reported that both temperature and velocity profiles decreases with increase in thermal stratification parameter In this work, we extended the work of Mukhopadhyay [13] by considering the influence of radiation on MHD boundary layer flow over an exponentially stretching sheet embedded in a thermally stratified porous medium with heat source and suction/blowing.…”
Section: Introductionmentioning
confidence: 99%
“…In many theoretical studies on heat transfer and fluid flow problems, the internal heat generation/absorption is assumed to be constant, space dependent or temperature dependent (non-uniform heat source/sink). The following researchers studied the effect of space- and temperature-dependent internal heat generation/absorption on the fluid flow problems recently (Manjunatha et al , 2014; Gireesha et al , 2017; Mabood et al , 2016).…”
Section: Introductionmentioning
confidence: 99%